Որոշիչ-որոշյալի կապակցության եղանակները ժամանակակից հայերենում և գերմաներենում - Շ. Գ. Ներսիսյան (ՀՀ ԳԱԱ հրատ.)
В современном армянском и немецком языках определения согласуются с определяемым посредством согласования, управления и примыкания. В зависимости от того, какой частью речи выражено данное определение, способы согласования в обоих языках разные. In Modern Armenian and German, the types of connection of attributive-constructions are adjunction, agreement and governance. In both languages, different methods of connection are used respective of what part of speech an attribute is expressed by.
Keywords: Philology; Linguistics; Language and Literature